Two-component adhesive composition
A two-component adhesive composition with a hydrolyzable silyl group and epoxy resin achieves rapid curing and stable adhesion, addressing the challenges of temporary fixation with double-sided tape in panel installation.
Patent Information
- Application Number
- JP2021031311
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-01
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-03-01
AI Technical Summary
Existing adhesives for fixing interior panels to base materials require temporary fixation with double-sided adhesive tape, which is difficult to peel off and affects workability, and the adhesive strength varies with mixing ratios, necessitating a solution for stable adhesion without tape.
A two-component adhesive composition comprising a compound with a hydrolyzable silyl group, epoxy resin, water, amine, and curing catalyst, with specific ratios to ensure rapid curing and stable adhesive strength.
The adhesive composition cures quickly and provides stable adhesion without temporary fixation, improving workability and ensuring consistent adhesive strength.
Smart Images

Figure 0007611730000001 
Figure 0007611730000002 
Figure 0007611730000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component adhesive composition containing a modified silicone resin, which is a compound having a hydrolyzable silyl group, and an epoxy resin. [Background technology]
[0002] When finishing the walls of a building, a method is used in which an interior panel such as a decorative panel is fixed to a base material such as a plasterboard with an adhesive. In this case, it is necessary to temporarily fix the interior panel to the base material until the adhesive hardens to prevent the interior panel from shifting or falling off, and a method is generally used in which a double-sided adhesive tape is used in combination to temporarily fix the panel with the double-sided adhesive tape, and then the panel is permanently fixed with the adhesive.
[0003] This method makes it possible to stably fix interior panels, but when double-sided adhesive tape is used for temporary fixation, it is difficult to remove once applied, making delicate alignment surprisingly difficult. In addition, it is time-consuming to peel off the release paper from the adhesive tape, which becomes waste and makes cleanup difficult, creating problems in terms of workability during installation.
[0004] In order to address these problems, a bonding method has been proposed that uses adhesive A containing a first polymer having an alkyldialkoxysilyl group and adhesive B containing a second polymer having a trialkoxysilyl group at the molecular end as an adhesive that does not require temporary fixing with double-sided adhesive tape (Patent Document 1). However, this method is time-consuming in that two types of adhesives must be applied separately, and there is a problem that the adhesive strength during temporary fixing is likely to vary depending on the application method because the pot life varies depending on the mixing ratio of the two types. Therefore, there has been a demand for an adhesive that can obtain stable adhesion in a short time after mixing the two liquids and can fix interior panels without temporary fixing with double-sided tape or the like. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5335507 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a two-component adhesive composition that cures in a short time after mixing of the base agent and the curing agent and has stable adhesive strength even without temporary fixation with a double-sided adhesive tape, and an adhesive method using the same. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides a composition comprising a base agent (A) containing a compound (a) having a hydrolyzable silyl group, an epoxy resin (b) and water (c), a tertiary amine (d), and The above (a) and a curing agent (B) containing a curing catalyst (e), wherein (a) is a (meth)acrylic polymer having a trimethoxysilyl group. and polypropylene oxide having a trimethoxysilyl group Including The amount of (a) in (A) is 60 to 97% by weight based on the total solid content. The adhesive composition is characterized in that
[0008] A second aspect of the present invention provides the adhesive composition according to the first aspect, characterized in that the amount of (b) in (A) is 2 to 30% by weight based on the total solid content.
[0009] The invention of claim 3 provides the adhesive composition according to either one of claims 1 or 2, characterized in that (B) further contains a plasticizer (f).
[0010] The invention of claim 4 is characterized in that the (f) is a (meth)acrylic polymer. Claim 3 The adhesive composition described herein is provided.
[0011] The invention of claim 5 is Claim The adhesive composition according to any one of 1 to 4 is used to adhere an interior panel material to a base material without temporary fixing. Effect of the Invention
[0012] The two-component adhesive composition of the present invention cures in a short time after the base agent and curing agent are mixed, and has stable adhesive strength, making it useful as an adhesive that can fix interior panels to base materials without the need for temporary fixation with double-sided adhesive tape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The main component (A) of the adhesive composition of the present invention contains a compound (a) having a hydrolyzable silyl group, an epoxy resin (b), and water (c), and the curing agent (B) contains a tertiary amine (d) and a curing catalyst (e). In this specification, the term "(meth)acrylate" includes both acrylate and methacrylate.
[0014] The compound (a) having a hydrolyzable silyl group used in the present invention is the main resin constituting the main agent (A) and is blended for the purpose of achieving high initial adhesion and rapid curing. The main skeleton may be a (meth)acrylic polymer, a polyalkylene oxide, or a polyisobutylene, but at least the main skeleton is a (meth)acrylic polymer structure and contains a compound having a trimethoxysilyl group as a hydrolyzable silyl group.
[0015] In the above (a), in order to lower the viscosity after mixing the main agent (A) and the curing agent (B) and at the same time improve the adhesion to the substrate, it is preferable to use a compound having a polyalkylene oxide main skeleton in addition to the main skeleton of the (meth)acrylic polymer structure. Examples of polyalkylene oxide include polyethylene oxide and polypropylene oxide. Examples of commercially available products include MA451 and MA480 (trade names: manufactured by Kaneka Corporation), which are mixtures of a (meth)acrylic polymer having a trimethoxysilyl group and a polypropylene oxide having a trimethoxysilyl group.
[0016] The amount of (a) is preferably 50 to 97% by weight, more preferably 60 to 95% by weight, and particularly preferably 70 to 90% by weight, based on the total solid content of the main component (A). By making it 50% by weight or more, sufficient initial tackiness to the finger touch and fast curing properties can be ensured, and by making it 97% by weight or less, sufficient planar tensile strength and workability can be ensured.
[0017] The epoxy resin (b) used in the present invention is blended for the purpose of increasing the hardness of the adhesive cured product and improving the planar tensile strength. Examples include aromatic epoxy resins such as bisphenol type and their hydrogenated products, alicyclic epoxy resins, aliphatic chain epoxy resins, isocyanurate type epoxy resins, glycidyl ester type epoxy resins, and glycidyl amine type epoxy resins. Among these, bisphenol type epoxy and aliphatic chain epoxy resins are preferred because of their low viscosity and good compatibility with (a).
[0018] Particularly preferred bisphenol type epoxy resins are bisphenol A type epoxy resins which have an epoxy equivalent of 170 to 200 and are liquid at room temperature, and bisphenol F type epoxy resins which have an epoxy equivalent of 160 to 185 and are liquid at room temperature. Also, examples of aliphatic chain epoxy resins include C4 to C8 diglycidyl ethers, and among these, hexamethylene diglycidyl ether is particularly preferred.
[0019] If the above (b) is blended with the hardener (B), the hardener (d) for (b) will be blended with the base agent (A), and in this case, the reaction between (a) and (d) will proceed in the presence of water (c) and thicken the base agent (A), resulting in a decrease in the shelf life of the base agent (A). Therefore, (b) must be blended with the base agent (A).
[0020] The amount of (b) is preferably 2 to 30% by weight, more preferably 3 to 25% by weight, and particularly preferably 8 to 18% by weight, based on the total solid content of the main component (A). By making it 2% by weight or more, sufficient planar tensile strength can be ensured, and by making it 30% by weight or less, sufficient compatibility and fast curing properties can be ensured.
[0021] The water (c) used in the present invention is blended to accelerate the curing speed when the base agent (A) and the curing agent (B) are mixed, to develop adhesive strength in a short time, and to improve deep curing. Examples include ion-exchanged water, distilled water, city water, and hydrous gel. Although adding (c) to the curing agent (B) improves deep curing, the catalyst easily reacts with water, and especially when a tin-based catalyst is used, it tends to hydrolyze, resulting in a decrease in storage stability and making it unsuitable.
[0022] The amount of (c) is preferably 0.3 to 5% by weight, more preferably 0.5 to 2.5% by weight, and particularly preferably 0.8 to 1.5% by weight, based on the total solid content of the main component (A). By making it 0.3% by weight or more, it is possible to ensure sufficient rapid curing properties and early development of adhesive strength, and by making it 5% by weight or less, it is possible to ensure sufficient storage stability.
[0023] The tertiary amine (d) used in the present invention is blended as a curing agent for (b) blended in the main agent (A). By using a tertiary amine, a cured product with high rigidity, high strength, and high elongation can be obtained. For example, piperidine, pyridine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, triethylenediamine, dimethylcyclohexylamine, dimethylbenzylamine, dimethylhexylamine, dimethylaminophenol, dimethylamino p-cresol, piperidine, 1,4-diazadicyclo[2.2.2]octane, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo[5.4.0]undecene-1, etc. can be mentioned, and they can be used alone or in combination of two or more kinds. Among these, 2,4,6-tris(dimethylaminomethyl)phenol is preferred because it has good reactivity, high adhesive performance, and is well-balanced in terms of availability and cost.
[0024] The amount of (d) is preferably 1 to 120 parts by weight, more preferably 5 to 100 parts by weight, and particularly preferably 10 to 80 parts by weight, per 100 parts by weight of (b) mixed in the main agent (A). By making it 1 part by weight or more, it is possible to ensure excellent curing properties after mixing, and by making it 120 parts by weight or less, sufficient storage stability can be ensured. A commercially available product is HISCAT HI-54K (trade name: 2,4,6-tris(dimethylaminomethyl)phenol, manufactured by KEUM JUNG Co., Ltd.).
[0025] The curing catalyst (e) used in the present invention is blended for the purpose of promoting the hydrolysis reaction of the alkoxy group, which is the hydrolyzable silyl group of (a) blended in the main agent (A), and improving the curing speed. Specific examples include metal compounds, amine compounds, carboxylic acids, etc., but metal compounds are preferred in terms of catalytic activity. Examples of metal compounds include tin, zirconium, titanium, aluminum, and bismuth compounds, which can be used alone or in combination of two or more. Among these, tin compounds are preferred in terms of their high activity as silanol condensation catalysts, and dibutyltin compounds are particularly preferred. Commercially available products include Neostane U-220H (trade name: dibutyltin diacetylacetonate, manufactured by Nitto Kasei Co., Ltd.).
[0026] The amount of (e) is preferably 0.1 to 8 parts by weight, more preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, per 100 parts by weight of (a) contained in the main agent (A). By making it 0.1 part by weight or more, sufficient curing properties can be expected, and by making it 8 parts by weight or less, sufficient adhesive strength and sufficient working time for work can be ensured.
[0027] The curing agent (B) of the present invention may further contain a plasticizer (f) in order to improve workability and adjust the hardness of the cured product. The plasticizer is preferably liquid at 25°C, and examples thereof include phthalate esters, aliphatic esters, polyesters, polyalkylene glycol esters, polyether polyols, epoxy, vinyl polymers, etc., and may be used alone or in combination of two or more. Among these, polymer plasticizers are preferred because they can adjust the mechanical properties of the cured product, such as tensile strength and elongation, and can suppress bleeding compared to low molecular weight plasticizers, allowing the initial physical properties to be maintained for a long period of time.
[0028] As the polymeric plasticizer, vinyl polymers are preferred because of their excellent weather resistance and heat resistance, and (meth)acrylic polymers are particularly preferred because of their excellent compatibility with (a). The weight average molecular weight (hereinafter Mw) is preferably 500 to 6000, more preferably 1000 to 3000. The viscosity at 25°C is preferably 100 to 3000 mPa·s, more preferably 200 to 2000 mPa·s. By setting the viscosity within this range, bleeding can be suppressed and the initial physical properties can be maintained for a long period of time, and compatibility with other components is good, making it easy to achieve an appropriate viscosity suitable for workability.
[0029] The amount of (f) can be adjusted as desired according to workability, and can be, for example, 0 to 150 parts by weight, preferably 30 to 130 parts by weight, and more preferably 50 to 120 parts by weight, per 100 parts by weight of (a) contained in the main agent (A). Commercially available (meth)acrylic polymers include ARUFON UP-1000 (product name: manufactured by Toa Gosei Co., Ltd., Mw 3000, viscosity 1000 mPa s) and UP-1020 (product name: manufactured by Toa Gosei Co., Ltd., Mw 1500, viscosity 400 mPa s).
[0030] To the composition of the present invention, a tackifier, a thixotropic agent, an adhesion promoter, an antioxidant, a leveling agent, an antifoaming agent, a thickener, a suspending agent, an antibacterial agent, an inorganic filler, organic fine particles, and the like may be added as necessary within the range not impairing the performance.
[0031] The base agent (A) and the curing agent (B) of the composition of the present invention are mixed immediately before use. Although the composition has the characteristic of a very fast curing speed, the pot life is relatively short, so it is preferable to use a two-liquid mixing and discharging device such as a static gun at the work site. By using such a coating device that can automatically mix a fixed amount, the workability at the work site can be significantly improved.
[0032] When using the present invention to bond interior panels such as decorative boards to substrates such as gypsum boards, calcium silicate boards, mortar surfaces, and plywood, a mixture of the base agent (A) and the hardener (B) is applied to one of the substrates, and the two are quickly bonded together. The application amount is 100 to 400 g / m. 2 is preferable, and 150 to 250 g / m 2 In this case, the weight per area of the interior panel to be bonded is preferably 1.0 g / cm. 2 If the thickness is less than 0.95g / cm2, it is possible to bond the material sufficiently without temporary fixing using double-sided adhesive tape. 2 Less than 0.90 g / cm is preferred. 2 The following is even more preferred:
[0033] The present invention will be described in more detail below with reference to examples and comparative examples, but these are illustrative examples and are not intended to be limiting. Unless otherwise specified, measurements were taken at 23°C and 50% relative humidity. The units in the recipes are parts by weight. EXAMPLES
[0034] Example 1 The main agent (A) side was MA451 (trade name: Kaneka Corporation, mixture of (meth)acrylic polymer having trimethoxysilyl group and polypropylene oxide having trimethoxysilyl group) as (a), bisphenol A type epoxy (epoxy equivalent 184-194, liquid at room temperature) as (b), and water as (c). The curing agent (B) side was HISCAT HI-54K (trade name: Keum Jung Corporation, 2,4,6-tris(dimethylaminomethyl)phenol) as (d), U-220H (trade name: Nitto Kasei Corporation, dibutyltin diacetylacetonate) as (e), and UP-1020 (trade name: Toa Gosei Corporation, acrylic polymer, Mw 1500, viscosity 400 mPa·s) as (f). Each was added to a planetary mixer in the amounts shown in Table 1 and stirred until uniform. After that, the main agent (A) and curing agent (B) of Example 1 were obtained by degassing under reduced pressure.
[0035] Examples 2 to 6 In addition to the materials used in Example 1, bisphenol F type epoxy (epoxy equivalent weight 165 to 180, liquid at room temperature) and hexamethylene diglycidyl ether were used as (b), and the base material (A) and the curing agent (B) of Examples 2 to 6 were obtained in the same manner as in Example 1.
[0036] Comparative Examples 1 to 9 In addition to the materials used in the examples, SAX-580 (product name: polypropylene glycol having a trifunctional trimethoxysilyl group, manufactured by Kaneka Corporation) and EST-280 (product name: polypropylene glycol having a bifunctional trimethoxysilyl group, manufactured by Kaneka Corporation) were used as (a) in the amounts shown in Table 2, and the base agent (A) and the curing agent (B) of Comparative Examples 1 to 9 were obtained in the same manner as in the examples.
[0037] Table 1 JPEG0007611730000001.jpg130135
[0038] Table 2 JPEG0007611730000002.jpg105135
[0039] Evaluation items and evaluation methods
[0040] Compatibility: The compatibility of the base agent (A) and the curing agent (B) was confirmed when each was prepared, and the state was visually checked 30 minutes after preparation. If the compatibility was good, it was marked with an ◯, and if separation or whitening occurred, it was marked with an ×.
[0041] Storage stability: The base agent (A) and hardener (B) were stored in a sealed container separately without being mixed, and left to stand for two weeks in an atmosphere of 40°C. After that, the base agent and hardener were mixed, and if there was no difference in the hardening time from the initial state and no increase in viscosity was observed in either agent, it was marked as ◯, and if there was a delay in hardening or an increase in viscosity, it was marked as ×.
[0042] Initial adhesion: The base agent (A) and hardener (B) were mixed and applied, and the adhesive was checked for adhesion by touching with a finger 10 minutes after hardening. If there was adhesion, it was marked as ◯, and if there was no adhesion or it was extremely weak, it was marked as ×.
[0043] Curing time: The base agent (A) and the curing agent (B) are mixed and applied in a bead shape with a diameter of 3.5 mm, and left to stand in an atmosphere of 23°C and 50% relative humidity. After a certain time has passed, the cross section is cut with a cutter. If the time it took for the inside to cure is within 5 minutes, it is marked as ○, and if it takes more than 5 minutes, it is marked as ×.
[0044] Plane tensile strength: A flexible board conforming to JIS A 5430 was used as the base material, and 3mmt x 40mm x 40mm AICA CERAALL FKM6000ZMN (product name: AICA Corporation, melamine resin-based non-flammable decorative board) was used as the surface material. The adhesive was mixed and applied in a bead shape with 3.5mmφ to the base material, which was then attached and cured for one week in an atmosphere of 23℃ x 50% RH to prepare a test piece. The plane tensile strength was then measured using a Construction Research Institute-type tensile tester, with 0.2MPa or more marked as ○ and less than 0.2MPa marked as ×. Measurements were taken from n=3, and the average value was used.
[0045] Evaluation results Table 3 JPEG0007611730000003.jpg65135
[0046] Table 4 JPEG0007611730000004.jpg52135
[0047] The examples were excellent with no problems in terms of compatibility, storage stability, initial adhesion, curing time, and flat tensile strength.
[0048] On the other hand, Comparative Example 1, which did not contain (e), and Comparative Example 3, which did not contain (c), were inferior in initial adhesion and curing time, Comparative Example 2, which did not contain (d), were inferior in initial adhesion, curing time, and flat tensile strength, and Comparative Example 5, which did not contain (b), had low flat tensile strength. Comparative Examples 4 and 6, in which (C) and (b) were blended in the curing agent side, were inferior in storage stability, Comparative Example 7, which used (a) that did not contain an acrylic polymer skeleton, was inferior in initial adhesion, and Comparative Example 8 was also inferior in curing time, and none of these were suitable for the present invention.
Claims
1. An adhesive composition comprising: a base agent (A) containing a compound (a) having a hydrolyzable silyl group, an epoxy resin (b) and water (c); and a curing agent (B) containing a tertiary amine (d) and a curing catalyst (e) for said (a), said (a) containing a (meth)acrylic polymer having a trimethoxysilyl group and a polypropylene oxide having a trimethoxysilyl group, said adhesive composition being characterized in that the blending amount of (a) in said (A) is 60 to 97% by weight based on the total solid content.
2. 2. The adhesive composition according to claim 1, wherein the amount of (b) in (A) is 2 to 30% by weight based on the total solid content.
3. 3. The adhesive composition according to claim 1, further comprising a plasticizer (f) in said (B).
4. 4. The adhesive composition according to claim 3, wherein the (f) is a (meth)acrylic polymer.
5. A method for adhering an interior panel material to a base material without temporary fixing, using the adhesive composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Automatic video tape reproducer
JP1978035507A
Moisture-curing adhesive composition
JP1992114078A
Silicone resin composition
JP1998251552A
Curable composition and method for producing the same, and cured product and sealing material
JP2017214541A
Curable composition
WO2006075482A1